Neology and Group Identification in Brazilian Funk Lyrics - da Costa, Daniel Soares [UNESP]; Andrade Nascimento, Geisibel Cristina [UNESP] (Springer Nature, 2023)
The objective of this chapter is to present a socio-semantic analysis of neologisms present in the lyrics of funk songs from Rio de Janeiro. Funk is a musical style that is linked to social issues, and, for this reason, the lyrics present some peculiarities that can be interpreted as marks of social identification. It can be noticed, in the reading of some lyrics of MCs, that, in addition to their global content, there is the use of specific words, which could be classified as slangs, to identify a particular social group. In our analysis, we were able to verify that, for the most part, these slangs consist in neologisms, mainly semantic neologisms. Because funk is a marginalized musical style, originating in the periphery and favelas of Rio de Janeiro, it is also our intention to contribute to the dissipation of the prejudice that surrounds this type of music, showing that certain words and linguistic constructions are representative of a dialect used by a particular linguistic community, which represents part of the diversity of uses of Portuguese. It is a work that involves the interaction between two areas of linguistic studies, neology and sociolinguistics, since it analyzes the use of new words, related to a type of linguistic variation of group identification.
Keywords: Funk; Group identification; Neologism; Variation